Program dan Kegiatan Humas Sekretariat Daerah Aceh Dalam Menjalankan Hubungan Media - Eva Hazmaini (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2019)
This article discusses the programs and public relations activities of Humas Sekretariat Daerah Aceh in carrying out relations with the media that are related to one another. PR programs and activities undertaken to build a positive image of government. The conceptual used is Public Relations within Government agencies according to Cutlip & Center. The method used in this paper is qualitative with a descriptive approach. The results of this study indicate that the efforts made by PR with the media through various formal and informal programs such as coffee morning, press releases, press conferences, hospitality with media leaders and so forth. Thus the relationship that exists between PR and the media can run well so that it can facilitate the Public Relations in publishing news about the Aceh government.